Integrating Modern Technology with Islamic Jurisprudence: The Role of Elsimil in Enhancing Family Resilience through Sadd Dzariah Perspective - Ahmad, Wildanil Musthafa; Syafi, Imam; Hariati, Nina Agus (JURNAL ISLAM NUSANTARA, 2024)
This research focuses on implementing Elsimil to increase family resilience and prevent stunting in children. This research uses library research methods. Primary data includes works such as "Ushul Fiqh" by Amir Syarifuddin, while secondary data includes books, articles, and other relevant literature. The findings of this study show that Elsimil contributes to family resilience by preventing stunting in children. This is achieved by early pregnancy planning and addressing early health problems. From the perspective of sadd dzariah, Elsimil is classified as neutral sadd dzariah by Ibn Qayyim, which involves using precautionary measures to avoid potential harm. Specifically, Elsimil serves as a means to prevent marital discord by offering early health intervention for expectant parents. Implementing Elsimil as a tool for family resilience, from Sadd Dzariah's perspective, is the right step. By planning pregnancies early and providing solutions for prospective brides and grooms, Elsimil helps prevent the birth of children with disabilities, thereby fostering household harmony. The implications of this research highlight the importance of integrating modern technological tools with traditional Islamic principles to increase family resilience and ensure the well-being of future generations.